2011
DOI: 10.1017/s0007114511006702
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of a mix ofLactarius deterrimusandCastanea sativaextracts on streptozotocin-induced oxidative stress and pancreatic β-cell death

Abstract: Pancreatic b-cell death or dysfunction mediated by oxidative stress underlies the development and progression of diabetes mellitus. In the present study, we tested extracts from the edible mushroom Lactarius deterrimus and the chestnut Castanea sativa, as well as their mixture (MIX Ld/Cs), for potential beneficial effects on streptozotocin (STZ)-induced pancreatic b-cell death. Analysis of chelating effects, reducing power and radical-scavenging assays revealed strong antioxidant effects of the C. sativa extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…Extracts of the chestnut inner shell (C. crenata) reduced oxidative stress in C57BL/6 mice exposed to a high-fat diet [24]. Similar results were reported by Grdović et al [35], who observed that spiny burrs extract of sweet chestnut (C. sativa Mill) reduced DNA damage induced by streptozotocin in pancreatic β-cells, and associated this reduction with the high content of ellagic acid and its derivatives in chestnut. In fact, ellagic acid was already known to reduce DNA damage in Chinese hamster ovary cells through comet assay and cytofluorimetric analyses [36].…”
Section: Oxidative Stress Parameters Group 1 (No Chestnut N = 6)supporting
confidence: 83%
See 1 more Smart Citation
“…Extracts of the chestnut inner shell (C. crenata) reduced oxidative stress in C57BL/6 mice exposed to a high-fat diet [24]. Similar results were reported by Grdović et al [35], who observed that spiny burrs extract of sweet chestnut (C. sativa Mill) reduced DNA damage induced by streptozotocin in pancreatic β-cells, and associated this reduction with the high content of ellagic acid and its derivatives in chestnut. In fact, ellagic acid was already known to reduce DNA damage in Chinese hamster ovary cells through comet assay and cytofluorimetric analyses [36].…”
Section: Oxidative Stress Parameters Group 1 (No Chestnut N = 6)supporting
confidence: 83%
“…Based on these results, dietary supplementation with edible chestnut does not seem to cause damage to DNA and it may even reduce oxidative DNA damage, in line with the findings of Jovanović et al [25], who showed that spiny burrs extracts of sweet chestnut reduce DNA damage in the liver and kidney cells of diabetic rats. This protective effect may be associated with the antioxidant properties of phenolic compounds in chestnuts [35]. Extracts of the chestnut inner shell (C. crenata) reduced oxidative stress in C57BL/6 mice exposed to a high-fat diet [24].…”
Section: Oxidative Stress Parameters Group 1 (No Chestnut N = 6)mentioning
confidence: 99%
“…Cell culture A rat INS-1 cell line, purchased from American Type Culture Collection (ATCC, Manassas, VA, USA), retains physiological characteristics of normal b cells. INS-1 cells (passages [10][11][12][13][14][15][16][17][18][19][20] were grown in RPMI 1640 medium (Hyclone, Logan, UT, USA), containing 6% fetal bovine serum (FBS) (vol./vol. ), 50 lmol/l b -mercaptoethanol, 1 mmol/l sodium pyruvate, 2 mmol/l L-glutamine, 100 U/ml penicillin, 100 lg/ml streptomycin (all from Sigma-Aldrich, St. Louis, MO, USA) and cultured at 37°C in a humidified atmosphere containing 95% air and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The mushroom L. deterrimus (Ld) was collected in the summer in Istria, Croatia. Cs and Ld extract preparation, their total phenolic and flavonoid contents and qualitative and quantitative analyses were performed using the HPLC/DAD method as described [9,14,15].…”
Section: Extraction Procedures and Characterization Of The Extractsmentioning
confidence: 99%
“…The flowers, fruits, leaves and skins of the sweet chestnut tree from the Fagaceae family, which grows in the Mediterranean region of Europe, have been widely used in folk medicine for treating various respiratory diseases [6,7]. Recent investigations have shown that the extract of the chestnut Castanea sativa possesses antiviral effects and the ability to lower oxidative stress and DNA damage [8,9]. Recent findings suggest that edible mushrooms are efficient antioxidants, possessing a radical scavenging activity whose antioxidant properties are effective in diabetes management [10].…”
Section: Introductionmentioning
confidence: 99%